‘I am’ Digital Stories for enabling the voices of autistic children and young people to contribute to educational decision-making and improve educational experiences - Sarah Parsons; Abigail Wright; Lowri Roberts; Jessica Lewis; Molly McGiveron; Hanna Kovshoff (Societal Impacts)
Educational and social experiences and outcomes remain poor for autistic children in Western educational systems. Transitions between stages of schooling and beyond mandatory education are times of particular challenge. Traditionally, to address these difficulties, there has been a tendency to focus on the difficulties experienced by young people rather than their strengths and interests, leading to deficit-focused approaches to thinking and support. To disrupt this status quo, we co-produced a strengths-based, transition-support approach with children, families and educators to encourage a positive change in attitudes, awareness, and practices amongst those who support children’s transitions. ‘I am’ Digital Stories draw upon the creative, arts-based method of digital storytelling to enable children and young people to contribute their voices to transitions and educational decision-making. Here we report on why this methodology is needed, what it entails, and provide an example of how it has been embedded in the practice of an Educational Psychology team within a local authority in Wales, UK, with impactful outcomes. This example shows how it is possible to make changes within local service provision that makes a difference to children and families and has wider implications for any service that supports autistic children and young people.